The effect of high-temperature intercritical annealing and rolling strain on the development of trimodal microstructure in low-carbon steel - Somayyeh Gholamalipour; Roohollah Jamaati; Seyed Jamal Hosseinipour (Journal of Materials Research and Technology)
In this work, the effect of high-temperature intercritical annealing and rolling strain on the microstructure and mechanical properties of low-carbon steel were studied. After intercritical annealing at the high temperature (830 °C), two different morphologies including lath and plate were formed for the martensite phase due to the short-term intercritical annealing treatment without prior homogenization. After the final heat treatment, the coarsest cementite particles belonged to the 25% deformed sample. In the microstructures of the 50% and 75% rolled samples, due to the larger number of preferred places for cementite precipitation (accumulation of dislocations), the number of cementite particles increased and their size became smaller. Recrystallization did not occur in the microstructure of the 25% + 550 sample owing to the low amount of rolling strain and static recovery (SRV) was the dominant restoration mechanism. However, in the microstructures of the 50% + 550 and 75% + 550 samples, static recrystallization (SRX) was the dominant restoration mechanism. Considering the presence of ferrite grains in three different categories (coarse, fine, and ultrafine) it can be concluded that the trimodal microstructure was formed in the 50% + 550 and 75% + 550 samples, while in the 25% + 550 sample, even the bimodal microstructure was not formed. The hardness, yield strength, and tensile strength of the heat-treated sheets were higher than that of the initial steel owing to the formation of fine spherical cementite particles and small (fine and ultrafine) ferrite grains. The ductile fracture was dominant in the fracture surfaces of the heat-treated samples. The results of the present work indicated that the formation of trimodal microstructure can be a promising approach to increasing the mechanical properties of plain carbon steels and their greater use in industries.